GAMIFICATION AND STUDENT MOTIVATION: EVALUATING E-LEARNING ENGAGEMENT FROM AN EDUCATIONAL PSYCHOLOGY PERSPECTIVE - Baso Intang Sappaile; Rachel Chan; Marcus Tan (Yayasan Adra Karima Hubbi, 2026)
Growing reliance on e-learning has transformed educational practice while simultaneously highlighting persistent challenges related to sustaining student motivation and meaningful learning engagement. Gamification has emerged as a promising instructional strategy that incorporates game design elements into digital learning environments to enhance learners' psychological involvement and academic performance. This study aimed to evaluate the effectiveness of gamification in improving student motivation and e-learning engagement from an educational psychology perspective by examining the relationships among motivational design, psychological needs satisfaction, learner engagement, self-regulated learning, and academic achievement. A mixed-methods sequential explanatory research design was employed, combining quantitative data collected from 480 undergraduate students through standardized motivation and engagement scales, academic performance assessments, and learning management system analytics with qualitative evidence obtained from classroom observations, semi-structured interviews, focus group discussions, reflective learning journals, and instructional document analysis. Findings revealed that students participating in gamified e-learning demonstrated significantly higher intrinsic motivation, self-efficacy, behavioral engagement, emotional engagement, self-regulated learning, and academic achievement than those enrolled in conventional online learning environments. Qualitative evidence further indicated that meaningful feedback, collaborative learning activities, learner autonomy, and active instructional facilitation strengthened the motivational impact of gamification. Results suggest that gamification functions most effectively when integrated with educational psychology principles, providing a sustainable pedagogical framework for promoting meaningful engagement, learner persistence, and long-term success in digital learning environments.